FREQUENCY OF CCR5?32 MUTATION IN BLOOD DONOR CANDIDATES FROM THE FUNDAÇÃO HOSPITALAR DE HEMATOLOGIA E HEMOTERAPIA DO AMAZONAS, BRAZIL - Guimaraes da Costa, Allyson; Monteiro Tarrago, Andrea; da Silva Abranches, Josilene; Pinto Garcia, Nadja; Vieira da Silva Neto, Pedro; Najibe dos Santos Ibiapina, Hiochelson; Sadahiro, Aya; Malheiro, Adriana (Revista de Patologia Tropical / Journal of Tropical Pathology, 2017)
The chemokine receptor CCR5 is a major co-receptor for HIV-1 entry into the host cell. Deletion of 32 bp (?32) alters the receptor structure and is associated with the protection against infection. The distribution of allelic variant depends on several factors influencing the epidemiology of HIV infections. Thus, the present study sought to estimate the allelic frequency of the CCR5 gene variant / CCR5?32 in blood donor candidates with and without positive serology for HIV-1+ at the HEMOAM Foundation. 239 candidates were enrolled and divided into two groups, HIV-1+ (101 individuals) and HIV- controls (138 individuals). After collecting peripheral blood, DNA was extracted and allele-specific PCR for identification of CCR5?32 polymorphism, was performed. The results obtained were analyzed using Stata (v.13). The groups were of similar ages, predominantly male and the distribution of genotypes and alleles were in Hardy-Weinberg equilibrium (p=0.725 and p=0.879, respectively). The highest frequency was wild genotype, followed by the heterozygous genotype in both groups (control and the HIV-1+ ). When the frequencies in HIV-1+ subgroups were analyzed, the absence of the allelic variant CCR5?32 subgroup ELISA(+) Westen Blot(+) was noted. Therefore, our data indicate that CCR5?32 polymorphism has a low frequency in the population studied.